(untitled) (Research in Agriculture Livestock and Fisheries, 2018)
The research was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh, to investigate the effect of time of split application of potassium on the yield of three transplanted (T) aman rice varieties. Rice varieties were BRRI dhan39, BRRI dhan40 and BRRI dhan41. Potassium was applied at the rate of 80 kg K ha-1. Experimental plot size was 5m2 (2.5m ×2.0m). Four split application of potassium [K1= Control (No K application), K2= 40 g K plot-1 at 15 DAT (days after transplanting), K3= 20 g K plot-1 at15 DAT+20 g K plot-1 at 30DAT, K4= 10 g K plot-1 at 15 DAT+ 10 g K plot-1 at 25DAT+ 10 g K plot-1 at 30 DAT+ 10 g K plot-1 at 45 DAT] were considered as treatments. From the experiment it was found that split application of potassium had no significant effect on plant height, length of panicle, thousand grains weight. It was evident that two splits application of potassium i.e., 20 g K plot-1 at 15 DAT+20 g K plot-1 at 30 DAT with BRRI dhan41 gave maximum no. of tiller hill-1, effective tiller hill-1, grains panicle-1, grain yield and straw yield, biological yield and harvest index. But varieties differed among themselves in terms of yield contributing characters and yield, and BRRI dhan41 performed the best. Therefore, based on the findings of the present study, it may be concluded that for obtaining higher yield BRRI dhan 41 can be grown following application of potassium at the rate of 80 kg ha-1 in two equal split at 15 and 30 days after transplanting Res. Agric., Livest. Fish.5(3): 313-320, December 2018